Квантовохімічне дослідження механізму окиснення аскорбінової кислоти молекулярним киснем на поверхні кремнезему - Demianenko, E. M.; Ilchenko, M. M.; Grebenyuk, A. G.; Lobanov, V. V. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2012)
The oxidation mechanisms have been studied of ascorbic acid molecule and monoanion with molecular oxygen in aqueous medium within the frameworks of density functional theory method with functional B3LYP, basis sets 6-31G(d,p) and 6-311++G(d,p), the CPCM model for solvent effect being applied. The interaction of oxygen molecule with partly dissociated ascorbic acid molecule under ambient conditions has been shown to be more profitable than that with undissociated ascorbic acid.